1990
DOI: 10.1210/mend-4-7-981
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β Induces Platelet-Derived Growth Factor (PDGF) Messenger RNA and PDGF Secretion while Inhibiting Growth in Normal Human Mammary Epithelial Cells

Abstract: Platelet-derived growth factor (PDGF) is a potent mitogen in human serum which specifically stimulates the proliferation of mesenchymal cells. We have now examined normal human mammary epithelial cells (HMEC) derived from reduction mammaplasties and grown in a serum-free defined medium. Medium conditioned by HMEC contained a PDGF-like activity that competed with [125I]PDGF for binding to PDGF receptors in normal human fibroblasts. When conditioned media were incubated with antiserum specific for either PDGF-A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
2

Year Published

1992
1992
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 0 publications
1
18
0
2
Order By: Relevance
“…22,54 Our studies now show that TGF-b can induce synthesis and secretion of PDGF-BB and PDGF-AB in ARPE-19 cells, similar to its ability to induce synthesis of PDGF and activate PDGF receptors in a variety of other cells. 20,21,55 Importantly, this induction of PDGF by TGF-b has recently been demonstrated to be Smad3/4 dependent, 56 consistent with absence of PDGF-BB expression in the KO RPE cells postretinal detachment. The Smad3 dependence of PDGF-BB expression in vivo further suggests that its expression is dependent on TGF-b rather than a direct result of the injury.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…22,54 Our studies now show that TGF-b can induce synthesis and secretion of PDGF-BB and PDGF-AB in ARPE-19 cells, similar to its ability to induce synthesis of PDGF and activate PDGF receptors in a variety of other cells. 20,21,55 Importantly, this induction of PDGF by TGF-b has recently been demonstrated to be Smad3/4 dependent, 56 consistent with absence of PDGF-BB expression in the KO RPE cells postretinal detachment. The Smad3 dependence of PDGF-BB expression in vivo further suggests that its expression is dependent on TGF-b rather than a direct result of the injury.…”
Section: Discussionsupporting
confidence: 53%
“…[13][14][15][16] TGF-b2 is expressed at much higher levels than the other TGF-b isoforms in the vitreous humor 12,17 and is a likely mediator of EMT in RPE cells in vivo, although the specific signaling pathways involved have not been identified. 5,18,19 Moreover, PDGF, TGF-b1 and CTGF are each known to be targets of TGF-b2 signaling, [20][21][22][23] suggesting that TGFb2 could orchestrate the secondary effects of these other peptides on EMT and fibrosis in PVR.…”
mentioning
confidence: 99%
“…Since it has been reported that SCC cell lines are frequently refractory to TGF-p activity 1421. this protein has been implicated as a possible mediator of angiogenesis [25,26] and a modifier of tumoral stroma. At later stages of carcinogenesis, TGF-p may condition the corium for tumor invasion.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-p types 1, 2, and 3 comprise a family of potential autocrine or paracrine growth-regulatory proteins of 25 kDa [16,231. Three TGF-p genes have been identified and characterized in mammals [241.…”
Section: Introductionmentioning
confidence: 99%
“…However, subsequent studies revealed that PDGF is also produced by the epithelium, endothelium, and many other cell types which are in close apposition to mesenchymal cells, which express PDGF receptors. These expression patterns suggest PDGFmediated paracrine signaling (Ataliotis and Mercola, 1997;DiCorleto and Bowen-Pope, 1983;Bronzert et al, 1990).…”
Section: Introductionmentioning
confidence: 90%